A numerical study of cool and green roof strategies on indoor energy saving and outdoor cooling impact at pedestrian level in a hot arid climate. Issue 1 (2nd January 2023) - Elnabawi, Mohamed H.; Saber, Esmail
Abstract : Green and cool roofs retrofit technologies, aim to mitigate the urban heat island effect and cooling energy demands from buildings. This study reports on parametric energy modelling of energy saving loads and indoor air temperature, as well as microclimate modelling of outdoor air temperature. The work adds new knowledge by evaluating roof retrofit technologies at the building and neighbourhood scale, and the results should guide strategic decisions for building envelope retrofitting. The simulations respectively predicted a 10% and 7.5% reduction in the cooling load for cool and green roofs versus a conventional roof. In summer, the indoor air temperature was similar for these roofs, but in winter the cool roof's indoor air temperature was 0.5°C lower than the green. In the microclimate simulation, average roof surface temperatures were 31.5°C (cool) and 31.3°C (green), versus 40.2°C (conventional); the air temperature difference was −0.8°C (cool) and −0.6°C (green) against the conventional roof.